The community corrections perspective toward sex offender management policies and collateral consequences: does contact with sex offenders matter?. Issue 1 (2nd January 2018) - Call, Corey
Abstract: Since the 1990s, numerous policies have been enacted aimed at managing sex offenders in the community. Two of the most prominent management policies are registries for sex offenders and residence restrictions. Community corrections professionals are tasked with enforcing these policies and yet little is known about their perceptions toward sex offenders and the policies in place to manage them. Prior research has suggested that contact with sex offenders may place a significant role in shaping the attitudes of community corrections professionals toward sex offender management policies and collateral consequences. The current study investigates the effect of contact with sex offenders on the perceptions of community corrections professionals ( n = 209) toward sex offender management policies and collateral consequences faced by sex offenders. Findings suggest that contact with sex offenders does not influence the attitudes of community corrections professionals, but several other significant factors were revealed including parental status, political orientation, race, tenure, sex, and age.